THE EFFECTS OF QUICK MASSAGE ON CHILD CARE (Fiep Bulletin - online, 2019)
Quality of life in the work environment is extremely important, healthy workers work with perform better. Work is animportant factor of physical, mental and psychological stress. It is increasingly common, to find workers with physiological andpsychological exhaustion, muscle pain and tension in workers. Occupational stress is directly related to the profession and the type ofwork performed, caregivers of children are exposed to several stressors, such as living with the indiscipline of the students, low levelof remuneration, restless routine with excess of activities at the same time and with little time devoted to health and well-being. Inthese cases, quick and effective procedures such as Quick Massage, are well accepted, help relieve stress-related symptoms,ensure relaxation, improve blood circulation, relieve tension and muscle pain. The technique can be carried out from 10 to 30 minutes,on the clothes and without need of products. The aim of this work is to investigate the improvement of well-being and the reduction ofstress based on the results of the physiological effects of Quick Massage. Fifteen volunteers, who were carers of children, wereselected to receive massage. Before and after the massage, blood pressure and heart rate were measured, and questionnaires wereapplied for stress level and satisfaction with the technique.
Keywords: massage; quick-massage; work stress